Reclapan: A Solution To Household Waste Issues Based on An Application To Promote Circular Economy - Elioting Bich Injesus; Retnaningsih; Suhendi (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: Waste management in Indonesia is an unresolved problem; factors such as inadequate facilities, ineffective management mechanisms, and community habits are the causesPurpose: This research aims to design solutions through application prototypes and business models that align with household waste management behavior, expectations, and problems.Design/methodology/approach: This research uses customer discovery and Lean Canvas methods, with 100 respondents at the problem test stage and 69 at the solution test stage. Findings/Result: The problem test showed that 86 percent of respondents experienced problems such as segregated waste being re-mixed during transportation, not having bins based on the type of waste, lack of frequency of waste transportation, far location of disposal sites, and inadequate disposal facilities. The solution is crafted by applying circular economy principles and packaged into an application that serves as a bridge between households facing waste management challenges and companies struggling to obtain quality recycling materials. Reclapan is an acronym for "Recycle Across the Planet for Nature." the name of the app reflects the concept of recycling as a global effort to maintain and restore the earth's natural conditions. Reclapan encourages creative and fun sorting actions with gamification features and rewards in the form of shopping vouchers and other features that can solve most household waste management problems.Conclusion: The "Reclapan" prototype was designed based on respondents' preferences and was considered more practical than current waste management practices. Given the positive response from respondents willing to use "Reclapan", it can be concluded that "Reclapan" effectively addresses the issue.Originality/value (State of the art): Reclapan is a prototype circular economy-based platform that connects households with companies that need high-quality raw materials from waste. Keywords: application prototype, customer discovery, circular economy, lean canvas, waste management